Are we lost yet? [4] : another Wallace the brave collection - Henry, Will (Henry, Will. Wallace the brave collection, 2022)
"Book 4 in the wonderfully imaginative Wallace The Brave series introduces an expanded and more diverse cast, including the dynamic, fan-favorite Rose, who gives Wallace a run for his money in kickball competitions, aquatic explorations, and other adventures. Together with Rose, Spud, Amelia, and the rest of their friends, Wallace enjoys a lifestyle of mischief, exploration, (and yes, school) that will thrill middle-grade readers while reminding their parents of the carefree, nostalgic appeal of Calvin & Hobbes and other classic comics."--Provided by publisher